TATA LAKSANA E-PROCUREMENT DI KABUPATEN BANYUMAS - LUTVI RIYANDARI (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2023)
The main purpose in this research is implementation understanding of E procurement also understand of supporting and E procurement obstacle factor in the pangkep district. E-procurement is an innovation in the use of Information Technology for the benefit of public services. Based on this, researchers are encouraged to try to explain the implementation of E-procurement in the Banyumas district. Amount of informan in this research are five people. type of research is qualitative with kind of fenomenology research which is focused on human living experiences. Collecting data technique are using observation method, interview and documentation. Data analysis using interactive analysis models. Research result refers to unoptimalitation of E procurement implementation in the Banyumas district. This implementation seen by the stage of the E procurement aspect altough appropriated absolutely unaccomplished. In accordance with the implementation exist in president regulation in article 107 year 2010 number 54. This can be seen indicator (1) E-tendering (2) E-bidding (3) Ecatalogue and(4) E-purchasing. Supporting factor in this implementation is strategy of loyalty provider whereas obstacles are divergents and postponement.